Akseptabilitas Sediaan Serbuk Boreh Bali dengan Scrub Beras Putih dan Kayu Cendana - Wahyu Wuryandari; Luh Ebi Ratna Anggriyani (LPPMKI - AKAFARMA AKFAR PIM, 2023)
The process of boreh preparation, which is quite time-consuming, and the use of white rice as scrubs, which is inconvenient, has caused traditional Balinese boreh to be rarely used, so it is necessary to innovate the dose form of boreh in the form of powder with white rice flour and sandalwood powder as scrubs. This study aims to determine the acceptability of Balinese boreh powder with white rice and sandalwood scrubs. The method included testing samples of boreh powder with and without sandalwood powder. The acceptability test was carried out on 30 respondents with the observation of preference, ease of use and feeling parameters. Each parameter has 2 questions. Finding shows that the highest acceptability preference parameter is found in formula 1 with each question getting a score of 46.80 and 47.20. In the parameter of ease of use, the highest acceptability is in the treatment of 15% rice flour and 15% sandalwood of 47.10 and 60.15. For the highest acceptability of feeling parameter is in the formula of 0% rice flour and 30% sandalwood of 50.23 and 51.63. In conclusion, the acceptability of the preference parameter is found in the treatment of 30% rice flour and 0% sandalwood, the ease of use parameter is in the treatment of 15% rice flour and 15% sandalwood, and the feeling parameter is in the treatment of 0% rice flour and 30% sandalwood.